2016
DOI: 10.1080/10942912.2016.1189434
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological activities of brown seaweed Sargassum wightii (Family Sargassaceae) using different in vitro models

Abstract: Recently a great deal of interest has been developed towards natural bioactive components from seaweeds as functional food ingredients. Antioxidant, anti-inflammatory, antidiabetic and antihypertensive activities of ethyl acetate:methanol (EM) and chloroform solvent fractions (CHCl 3 ) of the brown seaweed Sargassum wightii were evaluated using different in vitro systems. The EM fraction registered greater Fe 2+ ion chelating ability (IC 50 0.52 mg/ml), and were effective in stabilizing the ABTS .+ (IC 50 0.82… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(25 citation statements)
references
References 23 publications
0
24
0
1
Order By: Relevance
“…The results indicated the highest DPP-4 inhibitory activity from ethyl acetate : methanol fraction (IC 50 : 0.013 mg/ml) more than the chloroform fraction (IC 50 : 0.028 mg/ml) compared to the reference drug diprotein-A (IC 50 : 0.007 mg/ml). In addition, the ethyl acetate : methanol (2.51 mg GAE/g) and chloroform (2.04 mg GAE/g) fractions are rich in phenolic compounds which might be attributed to the DPP-4 inhibitory activity [54].…”
Section: Inhibitorymentioning
confidence: 99%
“…The results indicated the highest DPP-4 inhibitory activity from ethyl acetate : methanol fraction (IC 50 : 0.013 mg/ml) more than the chloroform fraction (IC 50 : 0.028 mg/ml) compared to the reference drug diprotein-A (IC 50 : 0.007 mg/ml). In addition, the ethyl acetate : methanol (2.51 mg GAE/g) and chloroform (2.04 mg GAE/g) fractions are rich in phenolic compounds which might be attributed to the DPP-4 inhibitory activity [54].…”
Section: Inhibitorymentioning
confidence: 99%
“…Studies on the anti-inflammatory activity of the Sargassum crude sulfated polysaccharides (CSP) have been carried out by several research groups [39,96,97,98,99,100,101,102,103,104,105,106,107] and are shown in Table 2. Sulfated polysaccharides (SP), such as fucoidan, carrageenan, and ulvan, are recognized as the typical functional compounds derived from various types of marine algae.…”
Section: Sargassum Species Are a Source Of Anti-inflammatory Agentsmentioning
confidence: 99%
“…The majority of Sargassum crude extracts tested on anti-inflammatory screening are derived from subtropical samples. Seventeen out of 73 studies used samples from tropical regions [34,35,36,39,40,41,42,43,44,45,47,48,49,51,52,53,54]. Most of the observed tropical species came from subgenus Sargassum , including S. polycystum, S. wightii, S. swartzii, S. crassifolium, S. binderi , and S .…”
Section: The Potency Of Tropical Sargassum As An Anti-inflammatorymentioning
confidence: 99%
“…SWE was less explored for its medicinal properties; only few studies have explained the biological activity of the crude extract prepared from S. wightii. [14][15][16] In the present study, S. wightii was fractionated using various solvents in Soxhlet extractor. Further, the solvent fraction was subjected to silica gel chromatography to partially purify and identify the solvent fraction rich in bioactive compounds with both ACE inhibition and antioxidant activity.…”
Section: Introductionmentioning
confidence: 99%